ECONOMIC ASSESSMENT OF THE EFFECTIVENESS AND QUALITY OF MANAGEMENT OF MEDICAL ACTIVITIES OF MEDICAL INSTITUTIONS (World Bulletin of Public Health, 2024)
Certainly! Exploring the economic assessment of the effectiveness and quality of management of medical activities within medical institutions unveils a complex interplay between financial performance, operational efficiency, patient outcomes, and strategic decision-making. This in-depth article will dissect the intricacies of measuring economic effectiveness in healthcare management, analyzing key performance indicators, cost-effectiveness, revenue optimization, and the impact of quality management practices on sustainable financial performance within medical institutions.